Exploring the role of ChatGPT voice conversation feature in improving EFL students’ speaking self-efficacy - Retno Tri Wahyuningtyas; Suparmi Suparmi (University of Muhammadiyah Malang, 2026)
This study aims to explore the role of ChatGPT's voice conversation feature in improving EFL students’ speaking self-efficacy. A qualitative design supported by quantitative data was employed, involving 21 students from the English Education department selected through purposive sampling. The data were collected through a questionnaire and semi-structured interviews. The questionnaire result revealed that students’ speaking self-efficacy was at a moderate level across all five dimensions: linguistic, communicative, task-specific, interactional, and affective self-efficacy. Meanwhile, the interview findings indicated that the ChatGPT voice conversation feature significantly enhanced students’ speaking confidence by providing real-time feedback, affirmative responses, and a natural human-like interaction. It also provided a non-judgmental environment that allowed students to practice speaking independently, serving as a motivating speaking partner. Hence, this study highlights the potential of the ChatGPT voice conversation feature as an AI-based digital tool that can be integrated into language learning to foster students’ speaking confidence and improve their speaking self-efficacy.